Photography and Cinema : 50 Years of Chris Marker La JetŒe - Medeiros, Margarida; Flores, Teresa Mendes; Leal, Joana Cunha (Cambridge Scholars Publishing, 2015)
Eclecticism seems to be one of the most recognized features of Chris Marker's work. He is often presented as a filmmaker and a photographer, a poet, a translator, a cartoonist, a visual artist, an editor, a software designer and a television and video director. Given the 50 years since the release of his most well-known film, La Jetée (1963), this volume fosters discussion of the intertwining of photography and cinema within a framework that analyses Marker's influence in film and photography's scholarship. In the last ten years, many books have been published on the subjects of photography and.